The effects of maturation on self-induced dynamic body sway frequencies of girls performing acrobatics or classical dance - Golomer, E.; Dupui, P.; Monod, H. (European Journal of Applied Physiology, 1997)
We investigated the effects of maturation on the dynamic body sways of healthy girls. Prepubertal and postpubertal girls practising professional physical activities requiring a good ability to maintain equilibrium (acrobats and dancers) were asked to stand on a free seesaw platform and the results compared to those for untrained age-matched girls. This platform (stabilometer) allows self-induced body sways. Stabilograms were obtained by a double integration of the angular acceleration from the recordings of the platform sways made with an accelerometer. Fast Fourier transform processing of stabilograms allowed spectral frequency analysis. The total spectrum energy and the energies of three frequency bands (0-0.5?Hz, 0.5-2?Hz, 2-20?Hz) were determined. ANOVA showed that, for all groups of different equilibrium activity and independent of visual input, prepubertal girls had higher energy values than postpubertal girls in the 0- to 0.5-Hz band whereas the opposite was true for 0.5- to 2-Hz band. Ballet dancers were more dependent than acrobats on visual inputs for the regulation of their postural control but were less dependent than untrained girls at both ages. Maturation seemed to shift body sways towards higher frequencies and the utilization of the cues of postural control was different according to the type of equilibrium activity practised by the subjects.